2022
DOI: 10.1101/2022.01.28.478036
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sex-specific regulation of binge drinking, social, and arousal behaviors by subcortical serotonin 5HT2creceptor-containing neurons

Abstract: Serotonin 5HT2c receptors have been implicated in the pathophysiology of both mood disorders and substance use disorders, but the precise cells and circuits mediating the effects on behavior have yet to be identified. In this study, we employed anatomical tracing, in-vivo fiber photometry with both calcium and serotonin sensors, electrophysiology, chemogenetics, and genetic manipulations of the 5HT2c receptor to identify two populations of neurons expressing serotonin 5HT2c receptors, one in the lateral habenu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 85 publications
0
5
0
Order By: Relevance
“…Instead, we could speculate that the reduced engagement to continue acquiring rewards is more strongly affected by the BNST under a low-effort regime, and more subtly under a high-effort regime. This hypothesis is also supported by the lack of effect on sucrose intake found under a FR4 regime upon BNST silencing (Flanigan et al 2023a) In any case, since the pace to obtain rewards is still affected under PR, these findings suggest that BNST CaMKIIa neurons play a role in motivation under both low-and high-effort paradigms.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…Instead, we could speculate that the reduced engagement to continue acquiring rewards is more strongly affected by the BNST under a low-effort regime, and more subtly under a high-effort regime. This hypothesis is also supported by the lack of effect on sucrose intake found under a FR4 regime upon BNST silencing (Flanigan et al 2023a) In any case, since the pace to obtain rewards is still affected under PR, these findings suggest that BNST CaMKIIa neurons play a role in motivation under both low-and high-effort paradigms.…”
Section: Resultsmentioning
confidence: 77%
“…It has been shown that GABA knockdown in CRF-expressing BNST neurons reduces motivation to work for sucrose, an effect that was selective for male mice (Gianessi et al 2023). In addition, while stimulation of serotonin 5HT(2c) receptor containing cells in the BNST reduces sucrose intake in only female mice (Flanigan et al 2023b), inhibition of these neurons does not seem to have an effect in both sexes (Flanigan et al 2023a).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, while we saw no effects of PVN CRH inhibition on female or male mice, male alcohol history mice spent significantly more time interacting with a juvenile mouse that water controls. Literature suggests that females are more likely to suffer from alcohol induced reductions in sociability (Flanigan et al, 2022;Sidhu et al, 2018;Simon et al, 2023), however, this is the first study to our knowledge that has investigated free social interaction in acute withdrawal from voluntary two-bottle choice alcohol consumption in mice.…”
Section: Slice Ex-vivo Electrophysiology In Pvn Crh Neuronsmentioning
confidence: 91%
“…During the sleep–wake cycle, the fluorescence signal changes are consistent with electroencephalography and electromyography recordings in the basal forebrain, the orbital frontal cortex, and the bed nucleus of the stria terminalis when measured in freely behaving mice using fiber photometry. Flanigan et al employed in vivo fiber photometry with the GRAB 5‐HT1.0 serotonin sensor to identify neurons that sex‐specifically coregulate affective behaviors and are modulated by binge alcohol consumption (Flanigan et al, 2022). Under two‐photon microscopy, the fluorescence changes maximally up to approximately 55% in behaving mice after injection of MDMA, which increases the serotonin level (Wan et al, 2021).…”
Section: Fluorescence Imaging Methods: Genetically Encoded Fluorescen...mentioning
confidence: 99%